(untitled) (Journal of Science and Technology, 2016)
Art works especially mural paintings, like all other scientific, historical and educational products of importance must enjoy a prolonged lifetime of aesthetic and functional benefit to society. Un- fortunately, the life span of outdoor murals displayed on public buildings in Ghana have been shortened by the ravages of weather, public interaction with them as well as deterioration over years of neglect. Many of such works especially those embedded in the walls of buildings come under severe defacement in the hands of building contractors who either smear them with wall paints or rip them off completely as irrelevant things when such edifices come under extensive renovation. Those that survive the test of time sadly end up with cracks. There seem to be the general lack of professional conservators with the right acumen for addressing the conservation needs of the country. This paper therefore throws a searchlight on preservation and retouching challenges and employs the descriptive method to discuss the researcher’s experience in retouch- ing five mural paintings at the Great Hall of KNUST, which had deteriorated and lost their aes- thetic values over years of neglect.